2018
DOI: 10.1002/bjs5.50125
|View full text |Cite
|
Sign up to set email alerts
|

National cohort study on postoperative risks after surgery for submucosal invasive colorectal cancer

Abstract: Background The decision to perform surgery for patients with T1 colorectal cancer hinges on the estimated risk of lymph node metastasis, residual tumour and risks of surgery. The aim of this observational study was to compare surgical outcomes for T1 colorectal cancer with those for more advanced colorectal cancer. Methods This was a population‐based cohort study of patients treated surgically for pT1–3 colorectal cancer between 2009 and 2016, using data from the Dutch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 32 publications
(28 reference statements)
2
46
3
Order By: Relevance
“…Male patients also showed the likelihood of increased postoperative complications. Previous studies have found that the rate of postoperative complications was significantly higher in male patients than that in female patients (34,35). The feature selection method showed no evidence of a patient's age being associated with prolonged LOS for patients undergoing CRC surgery.…”
Section: Discussionmentioning
confidence: 77%
“…Male patients also showed the likelihood of increased postoperative complications. Previous studies have found that the rate of postoperative complications was significantly higher in male patients than that in female patients (34,35). The feature selection method showed no evidence of a patient's age being associated with prolonged LOS for patients undergoing CRC surgery.…”
Section: Discussionmentioning
confidence: 77%
“…In this sense, it is relevant to improve the resection skills of the endoscopists in order to evaluate which lesions are at risk of harboring an invasive CRC candidate for endoscopic resection and, in any case, obtain a complete endoscopic resection according to the characteristics of the lesion. It is important to remind that endoscopic resection must enable the evaluation of the resection border [19,29]. As we have shown in this analysis, this is one of the discriminant variables associated with the risk of residual disease after endoscopic resection.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, surgery allows resecting completely and, thus, evaluates both the colon wall and the regional lymph nodes. Although it is associated with a low mortality risk, especially in the laparoscopic approach [19], it produces relevant short-and long-term complications [20]. Traditionally, in the decision-making analysis, the risk of death after surgery has been confronted with the risk of residual disease after endoscopic resection [17].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23] Most patients without LNM are routinely exposed to the risk of surgical resection with an associated postoperative mortality rate of 1.5% to 2% and no clinical benefit. 24 To reduce these unnecessary surgical resections and provide patients with proper treatment without excess or deficiency, development of a more accurate prediction model for LNM is necessary.…”
Section: Introductionmentioning
confidence: 99%